The influence of motivation, work culture and work environment on performance through empowering managers of village-owned enterprises (Bum Desa) in the Riau Islands Province - Maisuro Maisuro; Ngaliman Ngaliman; Gita Indrawan (Journal of Multidisciplinary Academic and Practice Studies, 2024)
Purpose: This research analyzes the influence of motivation, work culture, and work environment on the performance of Village-Owned Enterprise Management (Bum Desa) with empowerment as an intervening variable in the Riau Islands Province. Research Methodology: The study used A quantitative survey of 302 BUM Desa managers (sampled from 1,245 using Slovin’s formula) was conducted. Data were collected via Likert-scale questionnaires and analyzed using PLS-SEM with SmartPLS to test validity, reliability, and direct and indirect effects. Results: In 2023, of the 249 villages in the Riau Archipelago, only 10 (4%) were advanced and 34 (8.5%) developing, with most still basic. Using data from 302 managers, the study found that work culture and environment had no significant effect on empowerment, but together with motivation, they significantly improved performance. Conclusions: Motivation is the most critical factor for improving managerial performance, whereas empowerment strengthens the link between organizational culture, environment, and outcomes. Limitations: The study was limited to one province, and the results may differ in regions with stronger institutional and infrastructural support. Contribution: This research contributes to the development literature by highlighting the role of motivation and empowerment in improving BUM Desa performance, providing insights for policymakers and village leaders to strengthen the organizational capacity.